2021
DOI: 10.1590/interface.200267
|View full text |Cite
|
Sign up to set email alerts
|

Dimensão epistêmica da Reforma Psiquiátrica Brasileira: significados de gestores, profissionais e usuários

Abstract: O estudo objetivou analisar a dimensão epistêmica da Reforma Psiquiátrica Brasileira (RPB) sob a ótica de gestores, profissionais e usuários de serviços de saúde mental. Consiste em pesquisa qualitativa conduzida por meio de entrevistas semiestruturadas com 33 participantes e observação de campo na rede de atenção psicossocial de Vitória da Conquista, Bahia. O referencial teórico-metodológico fundamentou-se no campo epistêmico da RPB, com utilização de uma matriz analítica com três dimensões: concepção de saúd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…This finding is consistent with those found in other Brazilian regions [ 13 , 27 – 29 ] and international reports [ 2 , 30 ], reflecting the challenges of changing a logic limited to assistance to a users’ emancipatory scenario, which is necessary for community care in mental health [ 2 , 26 , 31 ]. In this sense, a paradigm change would require changes in how health professionals work, making it possible to break with the positivist principles and traditional psychiatry and find new ways of providing psychosocial care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with those found in other Brazilian regions [ 13 , 27 – 29 ] and international reports [ 2 , 30 ], reflecting the challenges of changing a logic limited to assistance to a users’ emancipatory scenario, which is necessary for community care in mental health [ 2 , 26 , 31 ]. In this sense, a paradigm change would require changes in how health professionals work, making it possible to break with the positivist principles and traditional psychiatry and find new ways of providing psychosocial care.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, recent qualitative research analyzing the points of view of mental health care network users [ 31 , 32 ] demonstrated that care processes are still marked by discrimination and limited social participation on a national scale. Mental health care networks and other social services are used when pathologies and the need for guardianship arise.…”
Section: Discussionmentioning
confidence: 99%
“…The struggle is to make the voice of those who experience mental suffering audible and validated. (2) This care model expands the view of what health is, giving prominence to the subjectivity of the subject, removing the focus of the use of psychotropic drugs as the only therapeutic form and valuing the use of light technologies in mental health promotion practices. (3) The theme of mental health care is comprehensive, being a dimension of human life present in all age groups, circumstances and environments.…”
Section: Introductionmentioning
confidence: 99%